Synaptocrine Signaling: Steroid Synthesis and Action at the Synapse - Saldanha, Colin J. (Endocrine Society, 2011)
Sex steroids have long been recognized for their dramatic impact on brain and behavior, including rapid modulation of membrane excitability. It is a widely held perception that these molecules are largely derived from peripheral sources and lack the spatial and temporal specificity ascribed to classical neuromodulatory systems. Neuromodulatory systems, in contrast, are defined by their regulated neuronal presynaptic secretion and by their functional modulation of perisynaptic events. Here we provide evidence for regulated presynaptic estrogen synthesis and functional postsynaptic actions. These results meet all the criteria for a neuromodulatory system and shift our perception of estrogens from that of peripheral signals exclusively to include that of a signaling system intrinsic to the brain itself. We apply the term synaptocrine to describe this form of neuromodulation.